Improving the inspection and manual cleaning of dental instruments in a dental hospital. Issue 1 (14th January 2016) - Campbell, Louise; Barton, Aisling; Boyle, Rachael; Tully, Vicki
Abstract: Within the dental hospital setting, it is a frequent occurrence to find residual cement contaminating instruments in a newly opened kit having undergone the decontamination cycle. Any instrument found to be contaminated then cannot be used, as the area underneath the cement is not sterile. This in itself has several repercussions. These include: cross-contamination, since there is a chance that the cement will be removed and the contaminated instrument used; cost, as each new kit that will be opened due to contaminated instruments will incur decontamination costs; and finally time, which most importantly has an impact on patient experience. Our baseline data recording focussed on finding out the severity of the problem, which instruments were most affected, and how this affected patient treatment, using a questionnaire. Within the paediatric department, 27% of examination kits contained a contaminated instrument, almost one third of all kits used. This quality improvement project utilized a poster and team huddle discussions to raise awareness of the problem and successfully reduced the number of contaminated instrument kits to 7% over a period of four weeks.